Perancangan UX Aplikasi Pembelajaran Pemanfaatan Smartphone untuk Optimalisasi Foto dan Video menggunakan Metode Human-Centered Design - Angel Anggina Nasution; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Digital technology that continues to develop has an impact on increasing smartphone users in Indonesia due to the ease of use. Based on the Ministry of Communication and Information data, smartphone users in Indonesia reached 167 million people, or 89% of the total population this year. The development of digital technology coupled with the Covid-19 pandemic is an essential factor that encourages MSME entrepreneurs to make adjustments. When marketing products digitally, photo and video processing is one thing that needs to be considered. The use of smartphones can be an easy and right choice for MSME entrepreneurs in processing photos and videos of their products or services to increase consumer interest. However, it is not uncommon for MSME entrepreneurs to experience difficulties when processing photos and videos of their products. So in this research, user experience design is carried out to help MSME entrepreneurs utilize their smartphones to optimize their products' photo and video quality. The method used in this research is the Human-Centered Design method because this method is generally used to develop interactive systems that suit user needs by considering user conditions. The final result of this research is a high-fidelity prototype used to test usability and user experience. The usability test results obtained are 85.71% on the effectiveness aspect using the completion rate metric, 0.059 goals/sec on the efficiency aspect using the time-based efficiency metric, and 84.5, which includes grade B, adjective rating Excellent, an acceptable category on the satisfaction aspect using the System Usability Scale (SUS) questionnaire. While the results of user experience testing using the User Experience Questionnaire (UEQ) show a value of 2.09 for the attractiveness aspect, 1.93 for the perspicuity aspect, 1.94 for the efficiency aspect, 1.66 for the dependability aspect, 2.04 for the stimulation aspect, and 1.54 for the novelty aspect.